2022
DOI: 10.1038/s41467-022-28443-0
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive strain sensors based on piezotronic tunneling junction

Abstract: Piezotronics with capacity of constructing adaptive and seamless interactions between electronics/machines and human/ambient are of value in Internet of Things, artificial intelligence and biomedical engineering. Here, we report a kind of highly sensitive strain sensor based on piezotronic tunneling junction (Ag/HfO2/n-ZnO), which utilizes the strain-induced piezoelectric potential to control the tunneling barrier height and width in parallel, and hence to synergistically modulate the electrical transport proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 46 publications
1
58
0
Order By: Relevance
“…ZnO (zinc oxide), a semiconducting material with a direct band gap of 3.4 eV and a large binding energy of 60 meV, exhibits many promising properties including piezoelectricity, pyroelectricity, and biocompatibility. 1 It attracts a lot of research attention and finds a variety of applications including luminescent materials, 2 sensors, 3 supercapacitors, 4 batteries, 5,6 solar cells, 7,8 and catalysts. 9,10 For catalytic applications, in particular, ZnO is a critical component of Cu/ZnO/Al 2 O 3 industrial catalysts for methanol synthesis from H 2 /CO/CO 2 11 and plays a very important part in the direct synthesis of light olefins from syngas 12,13 and propane dehydrogenation, 14 yet the detailed mechanisms are still under debate.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ZnO (zinc oxide), a semiconducting material with a direct band gap of 3.4 eV and a large binding energy of 60 meV, exhibits many promising properties including piezoelectricity, pyroelectricity, and biocompatibility. 1 It attracts a lot of research attention and finds a variety of applications including luminescent materials, 2 sensors, 3 supercapacitors, 4 batteries, 5,6 solar cells, 7,8 and catalysts. 9,10 For catalytic applications, in particular, ZnO is a critical component of Cu/ZnO/Al 2 O 3 industrial catalysts for methanol synthesis from H 2 /CO/CO 2 11 and plays a very important part in the direct synthesis of light olefins from syngas 12,13 and propane dehydrogenation, 14 yet the detailed mechanisms are still under debate.…”
Section: ■ Introductionmentioning
confidence: 99%
“…ZnO (zinc oxide), a semiconducting material with a direct band gap of 3.4 eV and a large binding energy of 60 meV, exhibits many promising properties including piezoelectricity, pyroelectricity, and biocompatibility . It attracts a lot of research attention and finds a variety of applications including luminescent materials, sensors, supercapacitors, batteries, , solar cells, , and catalysts. , For catalytic applications, in particular, ZnO is a critical component of Cu/ZnO/Al 2 O 3 industrial catalysts for methanol synthesis from H 2 /CO/CO 2 and plays a very important part in the direct synthesis of light olefins from syngas , and propane dehydrogenation, yet the detailed mechanisms are still under debate. , In these processes, the interaction between H 2 and ZnO is believed to be crucial , and has been investigated extensively. IR studies suggested two types of chemisorption of H 2 on ZnO in general, including type I featuring the formation of Zn–H and O–H, and type II with bridging hydride Zn–H–Zn and O–H···O species, and these hydride species were found particularly active for catalytic hydrogenation reactions .…”
Section: Introductionmentioning
confidence: 99%
“…Capacitive pressure sensors have high sensitivity and are mostly used in electronic skin and brain-computer interfaces, but their high sensitivity also makes them vulnerable to external interference [28] . Piezoelectric sensors are suitable for dynamic measurements and can respond quickly to pressure changes, but not for static tests [29] . The piezoresistive sensor has a simple structure, simple preparation, little in uence by external temperature and humidity, and has a certain scale production and application potential [30] .…”
Section: Introductionmentioning
confidence: 99%
“…Wearable sensors that transducing a physical stimulus into electrical signals can track human status and surrounding information by translating these physical stimuli into electrical signals 1,2,3,4 , which have played a vital role in the development of the Internet of Things 5,6,7 , soft robotics 8,9,10 , bioelectronics 11,12,13 , and artificial intelligence 14 . However, these conventional sensors face substantial challenges, such as difficulty in achieving conformable contact or 3D coupling with bio-tissues' curvilinearity.…”
Section: Introductionmentioning
confidence: 99%